KONSEP KEPEMIMPINAN POLITIK DALAM HADIS UMMUL HADIS: ANALISIS NILAI-NILAI KEPEMIMPINAN NABI - Fahril Hendrawan; Sri Mawaddah (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Political leadership in Islam is closely related to the exemplary behavior of the Prophet Muhammad SAW, who was not only a messenger of revelation, but also a leader of the people in all aspects of life, including politics. The Hadith of Ummul Hadith, namely the hadith "Indeed all deeds depend on the intention ..." is an important foundation in forming leadership values ​​that are oriented towards integrity and noble goals. This article aims to examine the concept of the Prophet's political leadership through an analysis of the values ​​in the Hadith of Ummul Hadith and their correlation with the Prophet's leadership practices in the context of statehood. This study uses a qualitative method with a descriptive-analytical approach to the hadith literature and the history of prophecy. The results show that the leadership of the Prophet Muhammad SAW is based on the values ​​of sincere intention (ikhlasiyyah), responsibility (mas'uliyyah), justice ('adalah), and exemplary (uswah hasanah) which can be used as guidelines in forming ethical political leadership that is oriented towards the welfare of the people.